Kinetic analysis of the hydrogen electrode reaction in unbuffered media. Theory and studies on Pt microelectrodes - Arce, Mauricio Damián (2013)
tThe hydrogen electrode reaction (HER) in steady state was described through a model involving mechanistic, mass-transport, and acid-base events. The model can be used to analyze polarization curves at any pH in conditions of high ionic strength and to obtain from these dependences the complete set of kinetic parameters. On the one hand, it involves the Volmer-Heyrovsky-Tafel (VHT) mechanism with H+ and H2(dis) at the electrode surface. On the other hand, the reaction of water dissociation at equilibrium is simultaneously considered as a source of H+ and HO-. The mass-transport by diffusion of H2(dis), H+ and HO- is included. In conditions of high mass-transport rates where kinetics plays an important role, the equations are able to reproduce the typical features that are observed in experimental current-potential curves in neutral and acid solutions (pH < 8). Besides, they can be used to analyze the dependence of the polarization resistance on the H+ concentration over this pH range. From these dependences, the elementary kinetic parameters of the VHT mechanism can be obtained, as it was demonstrated in this work on platinum microelectrodes.